Torsion in a paediatric wandering spleen: Case report and review of literature - Singla Sham Lal; Rattan K; Sharma Sachit; Bansal Satish (Wolters Kluwer Medknow Publications, 2007)
Pediatric wandering spleen is a clinical rarity. Generally it remains asymptomatic, but may present as a painless migratory lump in the left hypochondrium. Rarely it may present as acute abdomen after undergoing torsion over its pedicle leading to infarction and gangrene. Available treatment options include splenectomy or splenopexy. Splenectomy at times is associated with post-operative infections. Splenopexy may result in recurrent torsion.